2019
DOI: 10.3390/en13010063
|View full text |Cite
|
Sign up to set email alerts
|

Cantilevered Piezoelectric Micro Generator Design Issues and Application to the Mining Locomotive

Abstract: This paper will present a complete discussion in recent design strategies for harvesting vibration energy using piezoelectric cantilever transducers. The interest in this primary energy source is due to its presence in non-negligible quantities in most of the engines used in the industrial process. Previous work has shown that it is possible to harvest significant amounts of energy capable of supplying a wireless sensor (WS) node. However, in most research, only one step of the energy conversion and utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…The same observation can be made for the study in [38]. In [19] by considering most PT optimization solutions (in particular the SSHI technique), it is obtained that the vibrations took at a given moment in a mining locomotive make it possible to transmit data every 7 min at only 958 m, unlike every 1 min to 3 km as is the case in our study.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…The same observation can be made for the study in [38]. In [19] by considering most PT optimization solutions (in particular the SSHI technique), it is obtained that the vibrations took at a given moment in a mining locomotive make it possible to transmit data every 7 min at only 958 m, unlike every 1 min to 3 km as is the case in our study.…”
supporting
confidence: 70%
“…For example, in [38], it took 12 h of charging on a 0.33 pF capacitor before the sensor was able to transmit data. In [19], only 512 bits was transmissible every 7 min at less than one kilometer. This poor QoS is because most of the consumption models considered for stand-alone IWSs are based on short-range communication modules like the CC2520 from Texas Instruments.…”
Section: Msp430g2553mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, piezoelectric energy harvesting has demonstrated the ability to generate sufficient energy to power a wireless sensor node. Mouapi et al [126] designed a cantilevered piezoelectric energy harvester to scavenge the vibration of an operating mining locomotive. The recorded vibration data indicated that the test locomotive produced random vibrations with a dominant acceleration of 0.72 g at a frequency of 21.88 Hz.…”
Section: B Hardware Issuesmentioning
confidence: 99%